Effects of tillage management on cbbL-carrying bacteria and soil organic carbon dynamics across aggregate size classes in the farmland of North China Plain - Yao Yao; Xiaolin Shen; Lili Wang; Jianning Zhao; Lingxuan Gong; Su Wang; Linyi Wu; Gang Li; Weiming Xiu; Guilong Zhang (Ecological Indicators, 2023)
Calvin-Benson-Bassham cycle (cbbL)-carrying bacteria in soil are essential to renew and circulate organic matter. However, the relation between cbbL-carrying bacteria and soil carbon dynamics under tillage managements, especially across the aggregate size remains unclear. Thus, in our study, soil organic carbon (SOC) storages, mineralization, and the cbbL-carrying bacterial community across five soil aggregate sizes were thoroughly investigated under four tillage treatments: conventional rotary tillage (CT), deep plowing (DP), subsoiling (SS), no-tillage (NT). We found macroaggregates (>2 mm) contributed most with regard to SOC stocks, whereas microaggregates (<0.25 mm) contributed the least among all the tillage managements (NT, DP, SS and CT). Macroaggregates (>1 mm) with the highest cumulative SOC mineralization were found in subsoiling, whereas microaggregates had the lowest cumulative mineralization under no-tillage. By physically protecting, no-tillage specifically inhibited carbon dioxide (CO2) emissions in macroaggregates (>1 mm), whereas increased SOC levels and encouraged CO2 releases across microaggregates. Shifts in the co-occurrence network demonstrated that subsoiling promoted the joint symbiotic function between cbbL-carrying bacteria, the efficiency of matter and energy, and information transfer. And the keystone species, the enhanced cooperation and stochastic processes of autotrophic microorganisms under subsoiling lead to increased carbon fixation and reduced CO2 emissions in microaggregates with limited oxygen and nutrients. Overall, our work verified physical protection of large aggregates under no-tillage and improvement of microbial interaction efficiency under subsoiling. This may offer a theoretical foundation for the choice of tillage practices in fluvo-aquic soil regions.